Growing your business in emerging markets : promise and perils - Caslione, John A. (Quorum, 2000)
Annotation The future success of many companies in the United States and Europe is becoming more dependent on effectively developing and expanding markets in new emerging and partially developed countries. Few companies, however, know how to do it well, if at all. Their success rate is low, while the cost of failure remains high. Caslione and Thomas provide insights, knowledge, special tools, and the experience that will show executives how to take hold of these challenges. Through case studies of companies in a wide cross-section of industries, the authors highlight the processes necessary to develop successful market entry, sales, and distribution strategies for their companies in emerging markets around the world. Global business strategy can no longer be focused on only one country or region; the risks are too great. Only when a truly global company develops a holistic and global perspective and implements proven strategies can the success in the new global economy be achieved.